Pengaruh Model Pembelajaran Reciprocal Teaching terhadap Keterampilan Berbicara Siswa pada Pelajaran Bahasa Indonesia - Tiara Legiani; Gupo Matvayodha; Ilyas Idris (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aimed to analyze the effect of the Reciprocal Teaching learning model on the speaking skills of fifth-grade students in Indonesian language learning at MI Rahmatullah Jambi City. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The research was conducted at MI Rahmatullah Jambi City and involved 41 fifth-grade students, consisting of 20 students in the experimental class and 21 students in the control class. Data were collected through speaking tests, observations, interviews, and documentation. The data were analyzed using descriptive analysis, normality testing, homogeneity testing, and hypothesis testing through the Independent Samples t-test with the assistance of IBM SPSS Statistics version 27. The findings showed that the mean speaking skill score of the experimental class increased from 59.20 in the pre-test to 92.20 in the post-test, while the control class increased from 57.33 to 69.14. The hypothesis test showed a significance value (Sig. 2-tailed) of 0.037 (<0.05), indicating a significant difference between the experimental and control classes after the treatment. Therefore, it can be concluded that the Reciprocal Teaching learning model had a significant effect on the speaking skills of fifth-grade students in Indonesian language learning at MI Rahmatullah Jambi City